Impact of foreign direct investments on economic growth in Africa: Evidence from three decades of panel data analyses - (:unkn) unknown (My University, 2014)
This paper examines the impact of foreign direct investment (FDI) on economic growth in Africa and presents estimations based on panel data of 50 African countries during the period from 1980 to 2009, and the system generalized method of moment (SYS-GMM) estimators as proposed by Blundell and Bond (1998). It finds that FDI inflows had a significant impact on economic growth in the African region during the period of interest. It also finds that while the low level of human resources did not limit the impact of FDI, and that the impact of FDI on economic growth was negative during the period from 1980 to 1994 and positive during the period from 1995 to 2009.
Keywords: African Research